Pandangan Apoteker dalam Penerapan e-Prescribing di Rumah Sakit dan Farmasi Komunitas : Literatur Review - Muhammad Zaini; Muliyani Muliyani; Nazhipah Isnani; Husin Husin (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Electronic Prescribing is a system that utilizes information technology to replace or reduce the use of paper prescriptions in the process of prescribing medication to patients. The implementation of e-Prescribing poses significant challenges related to user readiness, facilities, and other factors. This study aims to determine the perspectives of hospital and community pharmacists on the implementation of e-Prescribing. The research design used in this paper is a literature review. The objects used in this study were taken from the results of research published in national and international journals. Articles were obtained from PubMed and Google Scholar using the keywords "Pharmacists" AND "Electronic prescribing" AND "Hospital". A total of 80 articles from PubMed and 280 articles from Google Scholar were obtained. The selection resulted in 6 articles that met the inclusion and exclusion criteria for use in this study. Based on the literature review of the 6 journals, information was obtained that the implementation of e-Prescribing from the perspectives of hospital and community pharmacists provides benefits in terms of ease of use, improving patient safety, speeding up service processes, and improving the quality of medication dispensing. Weaknesses identified in the implementation of e-Prescribing are associated with the availability of supporting facilities, skills and readiness of human resources, as well as the continued risk of medication errors.